Do managerial risk-taking incentives influence firms' exchange rate exposure? - Bill B. Francis; Iftekhar Hasan; Delroy M. Hunter; Yun Zhu (Bank of Finland, 2017)
There is scant evidence on how risk-taking incentives impact specific firm risks. This has implications for board oversight of managerial risk taking, firms' development of comparative advantage in taking particular risks, and compensation design. We examine this question for exchange rate risk. Using multiple identification strategies, we find that vega increases exchange rate exposure for purely domestic and globally engaged firms. Vega's impact increases with international operations, declines post-SOX, and is robust to firm-level governance. Our results suggest that evidence that exposure reduces firm value can be viewed, in part, as a wealth transfer from shareholders and debt-holders to managers.
URN:NBN:fi:bof-201708071455
Keywords: G32; 330